1995
DOI: 10.1021/es00008a007
|View full text |Cite
|
Sign up to set email alerts
|

Ozone Reactive Chemistry on Interior Latex Paint

Abstract: The heterogeneous chemistry of ozone on interior latex paint was investigated in a tube flow reactor. The emissions of several polar volatile organic compounds (VOCs) including organic acids and carbonyls (aldehydes and ketones) were measured while a glass tube coated with latex paint was exposed to clean air and ozone. Four different commercial brands of latex paint were tested. Formic and acetic acids were notfound to be generated via ozone reactions; however, both were found to off-gas from the latex paint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 14 publications
2
60
0
1
Order By: Relevance
“…Weschler et al 5 found in a laboratory study that ozone, which is present in indoor environments where there are appreciable ambient concentrations, reacts with carpet to form formaldehyde, acetaldehyde, and other C 5 -C 10 aldehydes. Reiss et al 6 have found that formaldehyde and acetaldehyde are formed from the reaction of ozone with latex paint. This indicates that ozone concentrations may affect indoor VOC concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Weschler et al 5 found in a laboratory study that ozone, which is present in indoor environments where there are appreciable ambient concentrations, reacts with carpet to form formaldehyde, acetaldehyde, and other C 5 -C 10 aldehydes. Reiss et al 6 have found that formaldehyde and acetaldehyde are formed from the reaction of ozone with latex paint. This indicates that ozone concentrations may affect indoor VOC concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…This factor was thus labeled ''secondary''. Reiss et al (1995b) found that aldehydes form from the reaction of ozone with latex paint. Similarly, Weschler et al (1992) found that in a laboratory study ozone reacted with carpet to form aldehydes.…”
Section: Factor Analysismentioning
confidence: 99%
“…For example, Sollinger et al (1994) report that the VOC emissions from carpets did not change with relative humidity over the range from 0 to 45% RH. On the other hand, the emissions of formic and acetic acids from latex paints have been reported to increase dramatically with relative humidity; for example, for one paint sample the emission rate for acetic acid almost tripled when the relative humidity was changed from 4-5% to 5-23% (Reiss et al, 1995b). A number of different aldehydes have been measured indoors (Crump & Gardiner, 1989;Lewis & Zweidinger, 1992;Zhang et al, 1994;Daisey et al, 1994;and Reiss et al, 1995a), some of which are directly emitted and some of which are formed by chemical reactions indoors of VOCs such as styrene.…”
Section: Volatile Organic Compounds (Vocs)mentioning
confidence: 99%